2016
DOI: 10.1002/2015jb012117
|View full text |Cite
|
Sign up to set email alerts
|

Pore‐scale simulation of carbonate dissolution in micro‐CT images

Abstract: We present a particle‐based method to simulate carbonate dissolution at the pore scale directly on the voxels of three‐dimensional micro‐CT images. The flow field is computed on the images by solving the incompressible Navier‐Stokes equations. Rock‐fluid interaction is modeled using a three‐step approach: solute advection, diffusion, and reaction. Advection is simulated with a semianalytical pore‐scale streamline tracing algorithm, diffusion by random walk is superimposed, while the reaction rate is defined by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
57
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 101 publications
(57 citation statements)
references
References 62 publications
0
57
0
Order By: Relevance
“…[] and Pereira Nunes et al . [] discussed how sample‐scale transport limitations imposed by a heterogeneous flow field are responsible for a decrease of one order of magnitude in the average reaction rate when compared to the batch rate. It was shown that this flow and reaction regime, termed “uniform” in Darcy‐scale studies, is actually a regime where the average dissolution rate is severely constrained by pore‐scale heterogeneities.…”
Section: Results: Average Dissolution Rates At High Péclet Numbersmentioning
confidence: 99%
See 4 more Smart Citations
“…[] and Pereira Nunes et al . [] discussed how sample‐scale transport limitations imposed by a heterogeneous flow field are responsible for a decrease of one order of magnitude in the average reaction rate when compared to the batch rate. It was shown that this flow and reaction regime, termed “uniform” in Darcy‐scale studies, is actually a regime where the average dissolution rate is severely constrained by pore‐scale heterogeneities.…”
Section: Results: Average Dissolution Rates At High Péclet Numbersmentioning
confidence: 99%
“…Here we summarize the assumptions and implementation of the particle‐based dissolution method introduced by Pereira Nunes et al . [].…”
Section: Fluid Flow Transport and Reactionmentioning
confidence: 99%
See 3 more Smart Citations